2017
DOI: 10.1139/cjpp-2016-0578
|View full text |Cite
|
Sign up to set email alerts
|

Vascular function and arginine and dimethylarginines in gentamicin-induced renal failure: a possible effect of heme oxygenase 1 inducer hemin

Abstract: Increased oxidative stress and disturbance in nitric oxide bioavailability lead to endothelial dysfunction and cardiovascular complication in renal disease. Gentamicin (GM), a commonly used antibiotic exhibits a toxic effect on renal proximal tubules. Prevention of its nephrotoxicity is important. Therefore, we investigated whether heme oxygenase (HO)-1 induction influenced kidney and vascular function in GM-administered rats. GM (100 mg/kg/day; ip) was given to rats alone or together with hemin (20 mg/kg/alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(20 reference statements)
1
2
0
Order By: Relevance
“…However, their relaxation was not affected upon the addition of sodium nitroprusside, an external non endothelium dependent vasorelaxant. Our data are in accord with the previous studies and indicates that GTN causes an impairment of endothelium dependent vasorelaxation [11,26]. A possible explanation of GTN-induced vascular dysfunction is impaired NO bioavailability in consequence to increased ROS production.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, their relaxation was not affected upon the addition of sodium nitroprusside, an external non endothelium dependent vasorelaxant. Our data are in accord with the previous studies and indicates that GTN causes an impairment of endothelium dependent vasorelaxation [11,26]. A possible explanation of GTN-induced vascular dysfunction is impaired NO bioavailability in consequence to increased ROS production.…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, renal injury induced by gentamicin could attenuate the vascular endothelium function. Evidence showed that gentamicin reduces renal levels of arginine, the rate limiting substance for nitric oxide synthase, leading to decreased nitric oxide (NO) [11]. The latter is derived from the endothelium and is essential for vasodilation, inhibition of platelet aggregation and inhibition of vascular smooth muscle proliferation.…”
mentioning
confidence: 99%
“…In this study, significantly upregulated mRNA expression of the HO-1 enzyme was observed in GMtreated rats in addition to an increase in HO-1 expression following supplementation with n-3 PUFA. It has been suggested that GM treatment induces a state of stress in cells by creating an inflammatory environment that may encourage expression of the HO-1 protein as a stress response (Duarte et al 2016, Aycan-Ustyol et al 2017, Park et al 2017). On the other hand, recent in vivo and in vitro studies postulated the ability of n-3 PUFA to induce HO-1 expression through direct activation of its upstream Nrf2 regulator gene (Qi et al 2017, Sakai et al 2017, Tatsumi et al 2019).…”
Section: Discussionmentioning
confidence: 99%